Re-Understanding the Hadith on Sexual Education Sigmund Freud's Perspective - Rofiatul Ubaidillah (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Understanding sexual education is considered necessary for adolescents. The lack of understanding of sexuality results in the misuse of sexual nature and the incompatibility of the function of sexuality experienced by humans themselves. This article describes the understanding of hadith on sexual education using Sigmund Freud's sexuality approach to human personality. That, human sexuality is formed with all the fixations during puberty, occurs due to the unfulfillment of sexual instincts that are so strong and there is repression during puberty. The type of this research is library research or library research, while the data obtained are primary and secondary data sources related to sex education. Hadiths about sexuality can be found in HR. Ahmad number 11173, musnad Abu Sa'id al-Khudri, History of Abu Dawud no. 3574 concerning women's clothing chapter. Hadith narrated by Qatadah RA about the prohibition of touching the genitals with the right hand. This article has implications for the formation of human sexuality, and how sexuality is used properly, according to the function of human sexuality.